Selection of Functional Human Sperm with Higher DNA Integrity and Fewer Reactive Oxygen Species. Issue 10 (17th April 2014) - Asghar, Waseem; Velasco, Vanessa; Kingsley, James L.; Shoukat, Muhammad S.; Shafiee, Hadi; Anchan, Raymond M.; Mutter, George L.; Tüzel, Erkan; Demirci, Utkan
Abstract : Fertilization and reproduction are central to the survival and propagation of a species. Couples who cannot reproduce naturally have to undergo in vitro clinical procedures. An integral part of these clinical procedures includes isolation of healthy sperm from raw semen. Existing sperm sorting methods are not efficient and isolate sperm having high DNA fragmentation and reactive oxygen species (ROS), and suffer from multiple manual steps and variations between operators. Inspired by in vivo natural sperm sorting mechanisms where vaginal mucus becomes less viscous to form microchannels to guide sperm towards egg, a chip is presented that efficiently sorts healthy, motile and morphologically normal sperm without centrifugation. Higher percentage of sorted sperm show significantly lesser ROS and DNA fragmentation than the conventional swim‐up method. The presented chip is an easy‐to‐use high‐throughput sperm sorter that provides standardized sperm sorting assay with less reliance on operators's skills, facilitating reliable operational steps. Abstract : Conventional sperm sorting methods employed in reproductive clinics to treat infertile couples involve centrifugation steps that damage sperm morphology and produce reactive oxygen species (ROS) and DNA fragmentation. Here, a centrifugation‐free high‐throughput sperm sorting assay that rapidly isolates functional sperm with high DNA integrity and fewer ROS is presented.